Biopsychosocial Factors Associated with Dysmenorrhea among High-School Girls in Makassar, Indonesia - Ruqaiyah Ruqaiyah; Ayatullah Harun; Alamsyah Alamsyah (Journal of Public Health and Pharmacy, 2026)
Introduction: Dysmenorrhea is a common menstrual disorder among adolescents and constitutes a significant public health concern due to its adverse effects on school attendance, academic performance, and quality of life. In low- and middle-income countries, including Indonesia, school-based evidence examining associations between biological, psychological, and lifestyle factors and dysmenorrhea remains limited. This study aimed to investigate associations between selected biopsychosocial variables and dysmenorrhea among senior high-school girls in Makassar, Indonesia. Method: A school-based cross-sectional study was conducted among 45 female students at SMA Bajiminasa Makassar using a total sampling approach. Data were collected through a structured, self-administered questionnaire assessing dysmenorrhea status, physical activity level, psychological stress, family history of dysmenorrhea, age at menarche, and menstrual cycle regularity. Descriptive statistics were used to estimate prevalence. Associations between variables were examined using bivariate analyses, including chi-square or Fisher’s exact tests when appropriate, and effect sizes were expressed as odds ratios (ORs) with 95% confidence intervals (CIs). Results: The prevalence of dysmenorrhea was 82.2%. Bivariate analyses indicated statistically significant associations between dysmenorrhea and inadequate physical activity, psychological stress, positive family history of dysmenorrhea, earlier age at menarche, and irregular menstrual cycles. Adolescents reporting psychological stress or a family history of dysmenorrhea demonstrated particularly high proportions of menstrual pain within this sample. Conclusion: Dysmenorrhea is highly prevalent among senior high-school girls in Makassar and was associated with several biological, psychological, and lifestyle variables examined in this exploratory analysis. These findings are consistent with biopsychosocial perspectives on adolescent dysmenorrhea, although the cross-sectional and bivariate analytical design limits causal interpretation. The results highlight the potential relevance of integrated school-based screening and health education initiatives addressing physical activity, psychological well-being, and menstrual health. Given the small sample size and single-school setting, findings should be interpreted cautiously and warrant confirmation in larger multi-site studies.